Desain Arsitektur Enterprise Berbasis Risiko Teknologi Informasi untuk Sistem Pelatihan: Integrasi COBIT 2019 dan TOGAF ADM - Desyaf Putra; Dinar Mutiara Kusumo Nugraheni; Jatmiko Endro Suseno (JST (Jurnal Sains dan Teknologi), 2025)
The increasing utilization of Information Technology (IT) in training implementation at the Agricultural Training Center (Bapeltan) Jambi presents challenges in IT risk management, system effectiveness, and infrastructure resilience. This study aims to identify the key IT risks faced by Bapeltan Jambi and design an Enterprise Architecture (EA)-based solution using TOGAF ADM with a risk analysis approach from COBIT 2019. The research methods employed include observations, interviews with various stakeholders, and risk analysis using APO12 (Manage Risk) in COBIT 2019. The research findings indicate that IT infrastructure disruptions, limited network capacity, data security vulnerabilities, and lack of system integration are the main factors affecting the effectiveness of training implementation. A total of 25 risk scenarios have been identified and categorized in the Risk Register, covering likelihood levels, impact, and mitigation strategies. Based on the analysis results, an enterprise architecture design based on TOGAF ADM has been developed with the models of Architecture Vision, Business Architecture, Information Systems Architecture, Technology Architecture, and Migration Planning to enhance the performance of IT-based training systems.